An Analysis of the implementation of the s-claim application system in the context of the implementation of BPJS claim standards in Charitas Belitang hospital in 2024 - Yunita, Ratna; Kasim, Felix; Ate Ginting, Keleng (JURNAL KESMAS DAN GIZI (JKG), 2024)
Background: The S-claim application is an application designed by the ICT team of Charitas hospital palembang to be used by the internal Charitas hospital group. This S-claim application is used by the service unit and the internal verifier of the casemix team at the hospital to make it easier to verify the completeness of the patient's file based on his diagnosis before being claimed to BPJS Kesehatan Objectives: to make efforts to improve the completeness of the claim file on the S-claim Application so that it is effective and efficient. Research method: This type of research is qualitative descriptive with data collection methods of interviews, observations and FGDs on 30 informants. Results: Based on the results of the study, it is known that the cause of the delay in BPJS Kesehatan claims is based on the input factor of the number of human resources that are not in accordance with the Job description, based on mathematical factors, namely incomplete hospitalization claim files such as medical resumes. Based on the Process factor, it is a Form Checklist of the completeness of the s-claim file that has not been running optimally in the authorized units.